The Stone Age of Indonesia. - Heekeren H. van (Brill, 1957)
This first edition of The Stone Age of Indonesia has been replaced by the second edition, which is published as Volume 61 (1972; ISBN 9024713005) in the series Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde.